(untitled) (REMUNOM, 2025)
The general objective of this paper is to analyze the economic situation of Americanas S.A. (AMER4) following the revelation of the largest corporate fraud in Brazilian history. To this end, the main techniques for economic valuation of companies, such as multiple analysis and Discounted Cash Flow (DCF), were addressed. The history and consequences of the accounting fraud involving the company were also investigated, as well as its performance during the judicial recovery process. The research adopts a quantitative and explanatory approach, using bibliographic and documentary procedures, with emphasis on the application of the DCF model, considered the most appropriate for valuing companies undergoing restructuring, complemented by statistical methods. At the end of the analysis, it was concluded that the DCF model proved to be effective in valuing companies in crisis. The study revealed that the fair value of the share was estimated at R6.54, consistent with the market price of R6.17 in the post-restructuring context. However, sensitivity analysis indicates that the value drops significantly to R2.89 under high-risk assumptions (WACC > 20%), reinforcing that the current pricing is not consolidated. The Americanas scandal profoundly impacted the Brazilian capital market, exposing governance weaknesses, but the company is showing signs of recovery supported by the capital injection and the Judicial Reorganization Plan. Sustaining market value requires the unquestionable consolidation of financial discipline and governance. Finally, it is concluded that the Americanas scandal left deep scars on the Brazilian financial market, highlighting governance and transparency flaws that need to be addressed. Even so, the company has shown signs of recovery, supported both by the capital injections received and the ongoing Judicial Reorganization Plan. To consolidate its market position and regain investor confidence, it will be essential to maintain strict financial discipline and strengthen corporate governance mechanisms to avoid new risks and ensure the business’s sustainability.